1996
DOI: 10.1089/aid.1996.12.143
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the Human Immunodeficiency Virus Long Terminal Repeat by CD8+T Cells Is Dependent on the NFAT-1 Element

Abstract: CD8+ T lymphocytes of HIV-1 infected individuals produce a soluble factor that efficiently suppresses HIV-1 replication at the transcriptional level. We show here that the response of the HIV-1 long terminal repeat (LTR) to mitogenic or Tat-mediated activation is sensitive to the suppressive action of a Herpesvirus saimiri (HVS)-transformed CD8+ T cell clone from an HIV-infected individual and supernatants from CD8+ T cells of HIV-1-infected asymptomatic subjects (CD4+ > 350/microliters). Mutagenesis of NF kap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 28 publications
4
30
0
Order By: Relevance
“…These results are in agreement with previous studies demonstrating that CAF mediates specific inhibition of LTR-driven activity (17,38). Copeland et al also showed that this inhibition may be mediated via the NF-B or the NFAT-1 element (18). Therefore, our data combined with these previous observations indicate that CAF is active at a post-reverse transcriptional level, and especially at the transcription level.…”
Section: Discussionsupporting
confidence: 94%
“…These results are in agreement with previous studies demonstrating that CAF mediates specific inhibition of LTR-driven activity (17,38). Copeland et al also showed that this inhibition may be mediated via the NF-B or the NFAT-1 element (18). Therefore, our data combined with these previous observations indicate that CAF is active at a post-reverse transcriptional level, and especially at the transcription level.…”
Section: Discussionsupporting
confidence: 94%
“…This transcriptional repression was observed in models mimicking both acute and chronic HIV-1 infection, as evidenced by suppression of LTR-activated transcripts in both TZM-bl and 8E5 cells. In the acute model, we found that the CD8 ϩ T-cellsecreted exosomes could suppress PMA-induced HIV-1 LTR transcription in the absence of tat or any viral protein expression, a result that is consistent with previous characterizations of the noncytotoxic antiviral activity in culture supernatant of CD8 ϩ T cells (5,12). Our results demonstrate that, unlike ␤-chemokines, the antiviral activity of exosomes was not mediated at the level of entry but through induction of an unknown signal that represses the lentiviral LTR promoter.…”
Section: Discussionsupporting
confidence: 90%
“…5B). The suppression of the PMA-activated LTR was especially significant since it demonstrated that the exosomes induced a transcriptional inhibition of the viral promoter independent of any HIV-1 protein expression, another hallmark of the noncytotoxic HIV-1-suppressing activity of CD8 ϩ T cells (11,12,42). To further confirm that LTR gene reporter expression was inhibited at the level of transcription, real-time RT-PCR analysis of ␤-galactosidase mRNA was performed on TZM-bl cells cultured in the absence and presence of antiviral exosomes.…”
Section: Characterization Of Cd8mentioning
confidence: 99%
“…We previously reported that while CD8 þ T cell supernatants suppress HIV-1 LTR-mediated gene expression in Jurkat T cells [18,19], an opposite effect was observed on gene expression in monocytic cells [22]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition to inhibition of HIV-1 replication in CD4 þ T cells and T cell lines, CD8 þ T cells mediate inhibition of LTR-directed gene expression in T cell lines [17][18][19][20][21]. We previously reported on the opposite effects of CD8 þ T cells on gene expression in T cells versus monocytic cells [22].…”
Section: Introductionmentioning
confidence: 99%